The Role of Parents in Learning To Improve The Quality of Early Childhood Education in Kindergarten Buah Hati of Tebo Regency, Jambi Province - Maryani, Eli; Yuliantina, Irma (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study explores the role of parents in early childhood learning, focusing on their role as motivators, facilitators, and role models. The research uses a descriptive analysis and qualitative approach, observing events related to parents' role in learning. The study concludes that parents play a crucial role in supporting children's overall development, providing emotional support, and praise. They also act as facilitators, providing facilities and infrastructure that support the child's learning process, such as books, stationery, and other learning materials. Parents can create a pleasant learning atmosphere at home, such as providing comfortable study rooms and helping children complete assignments. They can also actively participate in activities like collecting used media and loose parts for children's learning media. Parents also serve as role models, demonstrating good behavior in social interactions, respecting others, and having good moral values. These attitudes and behaviors serve as real examples for children in everyday life. Parents can also be brought to school as resource persons to provide inspiration for children's future lives. Involving parents in the learning process can significantly improve the quality of education.